Should professional interpreters be able to conscientiously object in healthcare settings?. Issue 10 (3rd December 2019) - Emmerich, Nathan; Phillips, Christine
Abstract : In a globalised world, healthcare professionals will inevitably find themselves caring for patients whose first language differs from their own. Drawing on experiences in Australia, this paper examines a specific problem that can arise in medical consultations using professional interpreters: whether the moral objections of interpreters should be accommodated as conscientious objections if and when their services are required in contexts where healthcare professionals have such entitlements, most notably in relation to consultations concerning termination of pregnancy and voluntary assisted dying. We argue that existing statements of professional ethics suggest that interpreters should not be accorded such rights. The social organisation of healthcare and interpreting services in Australia may mean those who have serious objections to particular medical practices could provide their services in restricted healthcare contexts. Nevertheless, as a general rule, interpreters who have such objections should avoid working within healthcare.